Boobie traps : a video documentary. - Goh, Fiona Yu Ming. (2008)
This report aims to trace the very beginnings of this film, form the sources of our inspiration, the research process, the production process, the difficulties we faced, the fun we had, our learning experience and last but most certainly not least, our feelings about this documentary.